2013
DOI: 10.1039/c3ra41325j
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, structure determination and synthesis of a trichlorodihydroxybibenzyl from a terrestrial plant

Abstract: A new natural product isolated from the leaves of the plant Anthurium aripoense found in Trinidad is shown by spectroscopic analysis and total synthesis to be 29,5,69-trichloro-2,39-dihydroxybibenzyl, a structure unprecedented in a higher plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…The compound was prepared as previously described [1] and was obtained directly by evaporation of a solution in ethanol as colourless prisms suitable for X-ray diffraction. The unit cell contained two closely similar independent molecules (the RMS between the two independent molecules, excluding H atoms is 0.11(1)), each involved in both intramolecular and intermolecular hydrogen bonding (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound was prepared as previously described [1] and was obtained directly by evaporation of a solution in ethanol as colourless prisms suitable for X-ray diffraction. The unit cell contained two closely similar independent molecules (the RMS between the two independent molecules, excluding H atoms is 0.11(1)), each involved in both intramolecular and intermolecular hydrogen bonding (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Some time ago we described the isolation, structure determination and synthesis of an unusual trichlorodihydroxybibenzyl derived from a terrestrial plant native to Trinidad [1]. In the course of the synthesis, the corresponding symmetrical dichlorodihydroxybibenzyl 1 (Figure 1) was obtained as a byproduct and subjected to full spectroscopic characterisation.…”
Section: Introductionmentioning
confidence: 99%
“…In another collaborative study with Dr Russel Ramsewak, following his visit to the University of the West Indies, the structure of the unusual trichlorodihydroxybibenzyl 58 isolated from a terrestrial plant was confirmed by total synthesis. 51 Alan's first research council-funded project examined an early example of what would now be termed organocatalysis, where highly functionalised achiral meso compounds were subjected to methanolysis in the presence of cinchona alkaloids. As shown in the example of 59 the resulting product containing six contiguous stereocentres is formed in reasonable enantiomeric excess, which for crystalline examples could be enhanced to a useful level by simple recrystallisation.…”
Section: O Phmentioning
confidence: 99%